Prevalence of Cardiovascular Risk Factors, Reperfusion Therapy and Mortality in Patients With ST-Elevation Myocardial Infarction in Elderly and Middle-ages - Parisa Janjani; Yaser Salehabadi; Sayeh Motevaseli; Reza Heidari Moghaddam; Soraya Siabani; Nahid Salehi (Sālmand, 2023)
Objectives The prevalence of cardiovascular risk factors is different in the elderly and middle-aged. Therefore the present study aims to compare the prevalence of risk factors affecting ST-elevation myocardial infarction (STEMI), type of treatment, and mortality rate in these two groups. Methods & Materials This retrospective cohort study included 1 071 elderly and middle-aged ST-elevation myocardial infarction (STEMI) patients who had referred to Kermanshah Imam Ali Hospital for 23 months from January 2017 to November 2019. Demographic information, cardiovascular risk factors, type of treatment, and mortality were examined. Data were analyzed with descriptive statistics, independent t test, and Chi-square test in Stata software version 14 with a significance level of 0.05. Results In the present study, the prevalence of risk factors, including smoking, high triglyceride, overweight, and obesity in the middle-aged group was significantly more than the elderly group (P < 0.05). The low-density lipoprotein (LDL) mean (mg/dL) in the middle-aged group (99.26 ± 71.69) was significantly higher than the elderly group (96.29 ± 8.5) (P < 0.05). The rate of primary angioplasty use was higher in the middle-aged (55.31%) than in the elderly (48.52%). Other results indicated that the overall mortality rate in the elderly (15.7%) was higher than in the middle-aged (4.4%) (P < 0.001). The prevalence of myocardial infarction, stroke, hypertension, hyperlipidemia, and glomerular filtration rate (GFR) < 60 was significantly higher in the elderly group compared to the middle-aged (P < 0.05). Conclusion The prevalence of low glomerular filtration rate (GFR), hyperlipidemia, and hypertension, myocardial infarction and stroke is higher in the elderly than in the middle-aged, while the prevalence of vital risk factors, such as smoking, triglycerides, overweight, and obesity in the middle-aged group is significantly higher than the elderly. If these risk factors are planned and controlled in middle age, people will be less at risk for myocardial infarction in aging.